RANGING RESULTS FOR TERRITORIES OF SIBERIAN AND FAR EASTERN FEDERAL DISTRICTS AIMED AT THE EVALUATION OF THE IMPACT OF TUBERCULOSIS CONTROL MEASURES ON THE EPIDEMIC SITUATION - T. V. Аlekseeva; O. V. Revyakina; O. P. Filippova; I. V. Pavlenok; T. I. Petrenko (Туберкулез и болезни лёгких)
Efficiency of tuberculosis control measures was comprehensively evaluated in the Russian regions (totally 21 regions) within Siberian and Far Eastern Federal Districts by means of ranging the sets of indicators. Three sets of indicators were used; these indicators reflected the epidemic situation and main rates of operation in the territories upon the outcomes of 2015. Totally 34 indicators were analyzed. The situation varies in different regions of Siberian and Far Eastern Federal Districts, the analyzed indicators significantly differ in the regions depending on the annual results, which first of all witnesses of differences in the quality and efficiency of tuberculosis control activities. Ranging as per indicators' set demonstrates the correlation between the epidemic situation and quality of tuberculosis control activities and stability of their level.